Adherence to the EAT-Lancet diet, plasma proteomics and the risk of chronic obstructive pulmonary disease - Lu, Xujia; Pei, Yalong; Geng, Yang; Fan, Yulong; Lu, Xinmei; Jiang, Lan; Borné, Yan; Ke, Chaofu (Thorax, 2025)
BACKGROUND AND AIMS: Adhering to the EAT-Lancet diet has been observed to be associated with lower risks of various morbidities. This study aimed to investigate the association of adhering to the EAT-Lancet diet with incident chronic obstructive pulmonary disease (COPD) and identify plasma proteins mediating such association. METHODS: This prospective study involved 202 340 participants free of COPD at baseline from the UK Biobank. Adherence to the EAT-Lancet diet was assessed by four different diet indices. Mediation effects of plasma proteins were investigated in a subcohort of 21 186 participants with information on plasma proteins measured by the OLINK Explore-3072 platform. RESULTS: Compared with individuals with the lowest adherence to the EAT-Lancet diet, those with higher adherence had a lower risk of developing COPD, and the HRs (95% CIs) for the highest adherence group versus the lowest were 0.607 (0.558 to 0.660) for the Willett EAT-Lancet index, 0.666 (0.593 to 0.748) for the Knuppel EAT-Lancet index, 0.586 (0.513 to 0.668) for the Stubbendorff EAT-Lancet index and 0.674 (0.620 to 0.732) for the Kesse-Guyot EAT-Lancet index. A total of 534, 149, 486 and 489 proteins showed significant mediation effects between the Willett, Knuppel, Stubbendorff or Kesse-Guyot EAT-Lancet index and incident COPD. The overall proteomic scores mediated 34.43% (95% CI: 22.86% to 53.45%), 24.15% (13.20% to 72.99%), 22.96% (14.53% to 41.13%) and 34.63% (21.26% to 60.38%) of the associations between the Willett, Knuppel, Stubbendorff or Kesse-Guyot EAT-Lancet index and incident COPD. CONCLUSION: Higher adherence to the EAT-Lancet diet was associated with a lower risk of COPD, and a wide range of circulating plasma proteins mediated such association.
© Author(s) (or their employer(s)) 2025. No commercial re-use. See rights and permissions. Published by BMJ Group.